The future was discussed at UNLPam. (Semiárida, 2024)
Foresight has a long tradition in Argentina, which began with the Bariloche Foundation's Latin American World Model in the 1970s. Since then, the discipline has seen advances and setbacks over time, but since the 2000s onwards, there has been a recovery and revaluation of the future dimension in the decision-making equation. The Argentine community of foresight experts grows year after year, in the quantity and quality of foresight studies developed and implemented, and the Prospecta Congresses have become a classic meeting between scholars and practitioners of the discipline. The first National Congress of Foresight - Prospecta Argentina was held in 2012 in Mendoza, organized by the Centro de Estudios Prospectivos of the Universidad Nacional de Cuyo together with the Ministry of Science, Technology and Innovation of the Nation. Subsequently, the 2014, 2017, 2022 editions were held, and up to this last edition in 2024 organized by the Facultad de Agronomía de la Universidad Nacional de La Pampa. The emphasis of this note is on sharing the central debates and agreements reached at the last National Congress on Foresight – Prospecta Argentina 2024. A meeting where experts, academics, consultants and referents analyzed the challenges and opportunities facing foresight and its fields of application in the coming years. Topics such as agricultural and food foresight, social and education foresight, territorial and environmental foresight, governance and prospective policy, economic foresight and sustainable development, foresight in innovation and technology, and Latin American Thought in Foresight were addressed. The participants highlighted the importance of developing prospective capacities to face future challenges and contribute to national and regional development. The note is a contribution to the collection of the discipline in Argentina.
Keywords: foresight; futures studies; development planning; social change; congress